KAJIAN MIMESIS DALAM NOVEL PESANTREN IMPIAN KARYA ASMA NADIA: A Study of Mimesis in Asma Nadia's Novel Pesantren Impian - Rifiatul Azizah; Aziz; Asia M (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2026)
This study aims to describe real-world issues using a mimetic approach in the novel Pesantren Impian by Asma Nadia. The method employed is qualitative research with a descriptive approach. The data source for this study is the novel Pesantren Impian by Asma Nadia. The data collected consists of quotations, sentences, and paragraphs that illustrate the social, economic, cultural, educational, and religious realities within Asma Nadia’s novel Pesantren Impian. The technique employed in this study is a literature review. The results of the data analysis indicate that a study of mimesis can be demonstrated by examining social, economic, cultural, educational, and religious realities. The findings reveal that in the social reality, the value of helping others is present. In the cultural reality, the value of belief or customs is found. In the educational reality, the value of curiosity is found. In the moral reality, the value of honesty is found. In the religious reality, a human connection in the form of gratitude is found